Mediation effect of body mass index on the association between spicy food intake and hyperuricemia in rural Chinese adults: the Henan rural cohort study - Xiaokang Dong; Yuqian Li; Kaili Yang; Lulu Zhang; Yuan Xue; Songcheng Yu; Xiaotian Liu; Runqi Tu; Dou Qiao; Zhicheng Luo; Xue Liu; Yan Wang; et al. (BMC, 2020)
Abstract Background The relationship of spicy food intake with hyperuricemia remains unknown. The objective of this study was to examine the association between spicy food intake and hyperuricemia, and whether this association was mediated by body mass index (BMI) in Chinese rural population. Methods 38, 027 adults aged 18-79 years were recruited from the Henan Rural Cohort Study. Information on spicy food intake was obtained using a validated questionnaire survey. Multivariable logistic regression model was used to estimate the association between spicy food intake and hyperuricemia, multiple linear regression model was performed to estimate the relationships between spicy food intake, BMI and serum urate level. BMI was used as a mediator to evaluate the mediation effect. Results After adjusting for potential confounders, compared with no spicy food flavor, the odds ratio (OR) and 95% confidence interval (CI) of mild, middle, and heavy flavor for hyperuricemia were 1.09 (1.00-1.19), 1.10 (0.97-1.24), and 1.21 (1.10-1.46), respectively (P trend = 0.017). Similarly, compared with those without intake in spicy food, the multivariable adjusted OR (95% CI) of 1-2 days/week, 3-5 days/week, and 6-7 days/week were 1.15 (1.01-1.31), 1.14 (1.01-1.30) and 1.15 (1.05-1.26), respectively (P trend = 0.007). However, when we further controlling for BMI, the associations were substantially attenuated. Furthermore, mediation analysis showed that BMI play a full mediating role in the relationship of spicy food intake with hyperuricemia. Conclusion Spicy food flavor and intake frequency are positively related with hyperuricemia in Chinese rural population. BMI may play a full mediating role in the relationship. Trial registration The Henan Rural Cohort Study registered at Chinese Clinical Trial Register (Registration number: ChiCTR-OOC-15006699 ). Date of registration: 2015-07-06.